2006
DOI: 10.1111/j.1748-1716.2006.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of methoxamine‐induced contractile responses of rat ventricular muscle in streptozotocin‐induced diabetes is associated with α1A adrenoceptor upregulation

Abstract: These results suggest that impairments of beta-adrenergic and Ca(2+)-handling mechanisms occur early in the development of cardiomyopathy in STZ-induced diabetic rats, and that this is followed by augmentation of alpha(1A) adrenoceptor-mediated inotropy due to alpha(1A) adrenoceptor upregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
2
11
1
Order By: Relevance
“…In 4 week STZtreated diabetic rats in our present study, we also found that it was predominantly the α 1A -AR mRNA and proteins that were up regulated while the α 1B -AR mRNA and protein were not altered in the diabetic rat hearts. However, we found an increase (not decrease, as in the study by Kamata et al, 2006) in the α 1D -AR mRNA in our study, along with undetectable α 1D -AR protein levels. The discrepancy between our study and the previous report (Kamata et al, 2006) on the direction of α 1D -AR change might be due to differences in the duration of the diabetic model (4 weeks vs. 10 weeks of STZ), animal strain (Sprague-Dawley rats vs. Wistar rats) and/or specificity of antibodies used.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…In 4 week STZtreated diabetic rats in our present study, we also found that it was predominantly the α 1A -AR mRNA and proteins that were up regulated while the α 1B -AR mRNA and protein were not altered in the diabetic rat hearts. However, we found an increase (not decrease, as in the study by Kamata et al, 2006) in the α 1D -AR mRNA in our study, along with undetectable α 1D -AR protein levels. The discrepancy between our study and the previous report (Kamata et al, 2006) on the direction of α 1D -AR change might be due to differences in the duration of the diabetic model (4 weeks vs. 10 weeks of STZ), animal strain (Sprague-Dawley rats vs. Wistar rats) and/or specificity of antibodies used.…”
Section: Discussioncontrasting
confidence: 48%
“…Early study in the 10 week STZinduced diabetic rats showed that α 1A -AR was significantly increased both at the mRNA and protein levels (Kamata et al, 2006). In these diabetic rats, although the α 1D -AR mRNA decreased significantly, the α 1B -AR mRNA was not altered (Kamata et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations